2021
DOI: 10.7759/cureus.14831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19-Associated Lockdown on Patients With Diabetic Retinopathy

Abstract: To evaluate the effect of the coronavirus disease 2019 (COVID-19)-related lockdown in the management of patients with diabetic retinopathy (DR), including diabetic macular edema (DME), in a tertiary reference center in Greece. MethodsIn this retrospective study, we first compared the number of patients who were diagnosed with DR or DME in our clinic during the period of the lockdown and during the same period of the previous year. In addition, we included consecutive patients with DR or DME, who were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…These findings in the study were comparable with various other studies done elsewhere. [11][12][13][14][15] The findings from the current study also suggested that refractive error (33.7%) and dry eyes (11.7%) are still the leading causes of ocular morbidity in both COVID-19 infected and non-infected study subjects. High prevalence of refractive error, dry eyes and to some extent computer vision syndrome (Table 1) in the study was attributed by the number of hours general population needed to stay at home and work through digital and social media during the pandemic and lockdown, this finding of the study also related well with pre COVID-19 era study done by Bastola P where refractive error and dry eyes were the most prevalent ocular diseases.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These findings in the study were comparable with various other studies done elsewhere. [11][12][13][14][15] The findings from the current study also suggested that refractive error (33.7%) and dry eyes (11.7%) are still the leading causes of ocular morbidity in both COVID-19 infected and non-infected study subjects. High prevalence of refractive error, dry eyes and to some extent computer vision syndrome (Table 1) in the study was attributed by the number of hours general population needed to stay at home and work through digital and social media during the pandemic and lockdown, this finding of the study also related well with pre COVID-19 era study done by Bastola P where refractive error and dry eyes were the most prevalent ocular diseases.…”
Section: Discussionmentioning
confidence: 62%
“…16 The evolution of positive clinical findings due to noncommunicable diseases like hypertension, diabetes mellitus, thyroid eye disorders, classical and common migraine (Table 1, 3) in the study has been explained well by comparable studies done elsewhere. [11][12][13] These findings were supported by the fact that due to COVID-19 pandemic and lockdown measures; the life style of general population was altered and modified which led to a more sedentary life style leading to aggravation of pre-existing hypertension, diabetes and thyroid disorder and new onset diabetic retinopathy and hypertensive retinopathy with mental health issues. In addition, the patients with diabetes and hypertension missed their routine follow ups for Ophthalmic examination during the COVID-19 pandemic and lockdown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One tertiary centre in Greece described the negative effect on visual acuity and progression to active PDR as a result of deferring appointments during lockdown [ 15 ]. Ghosal et al created a predictive model with regard to diabetic glycaemic control during lockdown using multivariate regression analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported an increased worsening of DR to active PDR post-lockdown. Postponement of care during pandemic was found to be the significant factor for worse visual outcomes [20]. In DME cases, there were unanticipated treatment delays due to lockdown that resulted in worsening and visual impairment [21].…”
Section: Discussionmentioning
confidence: 99%